Non è solo questione di cultura. Fattori di ostacolo e risorsa nella relazione famiglia-scuola dell’infanzia - Granata, Anna; Mejri, Ouejdane; Rizzi, Federica (Rivista Italiana di Educazione Familiare, 2015)
Family-school collaboration is a crucial element in achieving optimum scholastic experience on the part of pupils. Such collaboration is often described in somewhat reductive binary collaboration/non-collaboration terms. However, the significant presence of families from different cultural backgrounds in Italy since the 1990s demonstrates how multiple styles of relationships with schools can generate effective forms of collaboration. This paper analysed the case of family-school collaboration in infant schools in Milan, a privileged location where such dynamics can be investigated. Based on intercultural education approach and on in-depth interviews to infant school teachers and parents of pupils coming from different backgrounds, this research investigated different obstacles and resources that influence family-school relations. Results suggest that instead of an approach based just on cultural aspects, socio-economic, structural and interpersonal factors should be considered when approaching family-school relationship.